II. Rákóczi Ferenc itáliai (zarándok)útja - Takács, László (Antikvitás & Reneszánsz, 2018)
Young Ferenc Rákóczi traveled to Italy in 1693. His trip started in Vienna and then he visited Venice and other famous cities in Northern Italy, like Bologna, Florence, Pisa, etc. During his tour he spent four months in Florence, then he left for Torino, Milano, and in August he arrived in Loreto. Between September and January that year he was living in Rome. Later he traveled to Napoli and its neighbourhood. In February he had to return to Vienna. This journey was described by Rákóczi in his work named Confessio Peccatoris, which was composed in France more than twenty years later. Living in Paris and in the monastery of Grosbois Rákóczi was influenced by the contemporary Catholic theological movement called Jansenism. In this paper I will try to elucidate, how his Italian travel experiences were recomposed and reevaluated by Rákóczi two decades later under the influence in the framework of Jansenism.